Poly‐D, L‐lactic acid polymer and cochlear implantation. Issue 9 (19th September 2022) - Di Berardino, Federica; Messina, Federica; Conte, Giorgio; Cavicchiolo, Sara; Rossi, Diego; Giannì, Aldo Bruno; Pignataro, Lorenzo; Zanetti, Diego
Abstract: This case report describes a peculiar and innovative fixing procedure with a Poly‐D, L‐lactic acid (PDLLA) polymer in the unusual case of magnet dislodgment and rupture of the cochlear implant (CI) silicone sheath holding the magnet. Abstract : The poly‐D, L‐lactic acid (PDLLA) mesh provided excellent results in terms of stability, protection, preserved signal transmission and patient comfort avoiding explantation and re‐implantation of the CI in this case.